A complex species complex: The controversial role of ecology and biogeography in the evolutionary history of Syllis gracilis Grube, 1840 (Annelida, Syllidae). (15th November 2019) - Langeneck, Joachim; Scarpa, Fabio; Maltagliati, Ferruccio; Sanna, Daria; Barbieri, Michele; Cossu, Piero; Mikac, Barbara; Curini Galletti, Marco; Castelli, Alberto; Casu, Marco
Abstract: The cryptic diversity in the polychaete Syllis gracilis Grube, 1840, in the Mediterranean Sea was examined with an integrative morpho‐molecular approach. Individuals of S. gracilis were collected at eleven Mediterranean localities to provide an insight into the role of brackish environments in inducing cryptic speciation. The examination of morphological features combined with a molecular genetic analysis based on a partial sequence of the 16S rRNA gene highlighted discrepancies between morphological and molecular diversity. Morphological data allowed to identify a morphotype with short appendages occurring in coralline algae communities and another one with long appendages observed in brackish‐water environments and Sabellaria reefs. Multivariate analyses showed that sampling localities were the greatest source of morphological divergence, suggesting that phenotypic plasticity may play a role in local adaptations of S. gracilis populations. Molecular data showed the occurrence of four divergent lineages not corresponding to morphological clusters. Different species delimitation tests gave conflicting results, retrieving, however, at least four separated entities. Some lineages occurred in sympatry and were equally distributed in marine and brackish‐water environments, excluding a biogeographic or ecological explanation of the observed pattern and suggesting instead ancient separation between lineages and secondary contact. The co‐occurrence of different lineages hindered the identification of the lineage corresponding to S. gracilis sensu stricto. The discrepancy between morphological and molecular diversity suggests that different environmental and biogeographic features may interact in a complex and unpredictable way in shaping diversity patterns. An integrative approach is needed to provide a satisfactory insight on evolutionary processes in marine invertebrates. Abstract : The cryptic diversity in the polychaete Syllis gracilis was examined in eleven Mediterranean localities with an integrative morpho‐molecular approach. We observed a morphotype with short appendages in coralline algae communities and one with long appendages in brackish‐water environments and Sabellaria reefs. Sequences of the mitochondrial 16S rRNA gene revealed four divergent lineages not corresponding to morphological clusters. Some sympatric lineages were equally distributed in marine and brackish‐water environments, excluding a biogeographic or ecological explanation of the observed pattern, suggesting instead ancient separation between lineages.